2014
DOI: 10.1073/pnas.1324266111
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 10 is involved in induction of innate immune responses to influenza virus infection

Abstract: Toll-like receptors (TLRs) play key roles in innate immune recognition of pathogen-associated molecular patterns of invading microbes. Among the 10 TLR family members identified in humans, TLR10 remains an orphan receptor without known agonist or function. TLR10 is a pseudogene in mice and mouse models are noninformative in this regard. Using influenza virus infection in primary human peripheral blood monocyte-derived macrophages and a human monocytic cell line, we now provide previously unidentified evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(138 citation statements)
references
References 27 publications
2
133
1
2
Order By: Relevance
“…Briefly, lipoproteins are recognized by TLR1, TLR2 and TLR6; double-stranded and single-stranded RNAs by TLR3, TLR7 and TLR8; LPS by TLR4; flagellin by TLR5; and DNA by TLR9. 11 Although recent evidence suggests that TLR10 could have either immune-stimulatory 12 or immune-suppressive 13 properties, its exact activating ligand(s) and function are not yet known. TLRs signal through five different adaptor molecules: myeloid differentiation primary response gene 88 (MyD88), MyD88 adaptor-like (Mal), TIR-domain containing adaptor protein-inducing IFN-b (TRIF), TRIF-related adaptor molecule (TRAM) and sterile armadillo-motif-containing protein (SARM).…”
Section: Pathways Triggering Production Of Type-i-ifnsmentioning
confidence: 99%
“…Briefly, lipoproteins are recognized by TLR1, TLR2 and TLR6; double-stranded and single-stranded RNAs by TLR3, TLR7 and TLR8; LPS by TLR4; flagellin by TLR5; and DNA by TLR9. 11 Although recent evidence suggests that TLR10 could have either immune-stimulatory 12 or immune-suppressive 13 properties, its exact activating ligand(s) and function are not yet known. TLRs signal through five different adaptor molecules: myeloid differentiation primary response gene 88 (MyD88), MyD88 adaptor-like (Mal), TIR-domain containing adaptor protein-inducing IFN-b (TRIF), TRIF-related adaptor molecule (TRAM) and sterile armadillo-motif-containing protein (SARM).…”
Section: Pathways Triggering Production Of Type-i-ifnsmentioning
confidence: 99%
“…Human TLR10 recognizes ligands from listeria in collaboration with TLR2 (Regan et al, 2013), whereas mouse TLR10 contains a stop codon and, thus, it is a pseudogene (Kawasaki and Kawai, 2014). TLR10 also responds to influenza A virus infection (Lee et al, 2014). Mouse TLR11 detects flagelin (Madhur et al, 2010), a component of uropathogenic bacteria , and binds to the Toxoplasma gondii profiling protein (Yarovinsky et al, 2005).…”
Section: A Structure and Functionmentioning
confidence: 99%
“…The increase in TLR10 expression also seen in their study possibly corroborates the hyperactivity of the body to viral infections in contact with both of metal-oxide nanoparticles. Even though the receptor TLR10 still has unknown functions, a study has demonstrated its role as a sensing receptor for virus in human macrophages [31].…”
Section: Nanomaterials Recognition By Macrophagesmentioning
confidence: 99%